POLA ASUH ORANG TUA TERHADAP MENINGKATKAN KEMAMPUAN BERKOMUNIKASI ORAL PADA ANAK TUNARUNGU DI KELAS IV SLB PRIMA BAKTI MULIYA CIMAHI - Friska Aprillia Sidiq, - (2021)
This study aims to describe: 1) how parenting is applied by parents 2) how children's communication skills 3) how parents apply parenting to develop children's achievement in communicating This research is a descriptive study with a qualitative approach. The subjects of this study were the parents of the 4th grade Prima Bakti Mulia Special Children School students. Data was collected using observation, documentation and interview techniques. The data analysis technique used qualitative data analysis with interactive methods which include data collection, data presentation, data reduction and drawing conclusions. The validity of the data used in this study was source triangulation. The results used three subjects, parents, teachers and students with the results that parents of students generally applied parenting at home to improve oral communication skills 1) ZR's parents, Mr, Af provide exercises to their respective children in effort to improve their oral communication skills 2) Zr's ability to communicate is good, Mr.'s orally is quite good, Af's orally is said to have a clear ability 3) Zr's parents implemented early intervention, Mr's parents not give special treatment to Mr, Af's parents gave more treatment to Af. Zr and Af's parents apply democratic parenting while Mr's parents apply permissive parenting.